226Ra and 210Po concentration in drinking water of Cauvery river basin south interior Karnataka State, India. Issue 1 (January 2017) - Kavitha, E.; Chandrashekara, M.S.; Paramesh, L.
Abstract: Naturally occurring radionuclide 210 Po which is an element of 238 U decay series, contribute to the radiation that normally people are exposed. Drinking water samples collected from Cauvery river basin of south interior Karnataka State, India were analysed for the activity of 210 Po using radiochemical analysis technique. The estimated concentration of 210 Po in river water ranges from 0.86 to 4.49 mBq l −1, and its mean value is 2.67 ± 1.09 mBq l −1 . The concentration of 210 Po in bore well water ranges from 1.89 to 4.18 mBq l −1 and its mean value is 3.22 ± 0.67 mBq l −1 . The dissolved radium concentration in river water varies from 9.09 mBq l −1 to 55.07 mBq l −1 with an average of 32.33 ± 14.16 mBq l −1 . Total ingestion dose rate due to 226 Ra and 210 Po varies from 2.61 to 15.00 μSv y −1 with a mean value of 8.95 ± 3.74 μSv y −1, which is less than the recommended value by ICRP (International commission on radiological protection).